Analysis of gut microbiota in three species belonging to different genera (Hemitragus, Pseudois, and Ovis) from the subfamily Caprinae in the absence of environmental variance. Issue 17 (31st July 2021) - Sun, Guolei; Xia, Tian; Wei, Qinguo; Dong, Yuehuan; Zhao, Chao; Yang, Xiufeng; Zhang, Lei; Wang, Xibao; Sha, Weilai; Zhang, Honghai
Abstract: This study aimed to identify the effects of host species on the gut microbial flora in three species ( Hemitragus jemlahicus, Pseudois nayaur, and Ovis orientalis ) from the subfamily Caprinae, by excluding the impact of environment factors. We investigated the differences in intestinal flora of three species belonging to Caprinae, which were raised in identical conditions. Fecal samples were collected from tahr, mouflon, and bharal, and the V3–V4 region of the 16S ribosomal RNA gene was analyzed by high‐throughput sequencing. The analysis of 16S rRNA gene sequences reveals that fecal samples were mainly composed of four phyla: Firmicutes, Bacteroidetes, Spirochaetes, and Proteobacteria. The most abundant phyla included Firmicutes and Bacteroidetes accounting for >90% of the bacteria, and a higher Firmicutes/Bacteroidetes ratio was observed in tahrs. Moreover, significant differences existed at multiple levels of classifications in the relative abundance of intestinal flora, differing greatly between species. Phylogenetic analyses based on 16S rRNA gene indicated that mouflon is closely related to bharal, and it is inconsistent with previous reports in the species evolutionary relationships. In this study, we demonstrated that the gut microbiota in tahr had a stronger ability to absorb and store energy from the diet compared with mouflon and bharal, and the characteristics of host–microbiome interactions were not significant. Abstract : We investigated the differences in intestinal flora of three species belonging to Caprinae living in the same environment and raised in identical conditions. We demonstrated that the microbiota in tahr had a stronger ability to absorb and store energy from the diet compared with mouflon and bharal, and the characteristics of host–microbiome interactions were not significant.